RESPON SPESIFIK PUSKESMAS TERHADAP KEBUTUHAN SANITASI PENDUDUK PERMUKIMAN KUMUH DI BANTARAN SUNGAI CODE, KOTA YOGYAKARTA - Relmbuss Biljers Fanda; Mubasysyir Hasanbasri; Retna Siwi Padmawati (Journal of Health Service Management, 2016)
Background: Gondomanan Primary Health Care (PHC) have the toughest slums in the Code River, which Prawirodirjan village, but has made a declaration STBM in 2013. Objetive: To understand specifific response of PHC to sanitation need of slum dweller in Code riverbank in Yogyakarta. Method: This research used a qualitative method. This study used the case study, and data collection techniques in depth interview. This research held in Prawirodirjan village. The participants of this research were included 16 people, that consist of employees of Gondomanan PHC and Ministry of Health (MOH), infrastructure, enviroment agency, The Head Prawirodirjan village, cadre of CLTS and slum communities. Results: CLTS that implemented in Gondomanan PHC has reached the stage of the declaration. Gondomanan performs the function of empowerment and coordination with other stakeholders in CLTS with open defecation free (ODF). However, the achievement of the declaration still leaves problems, namely the wrong faeces disposal, the diffiffifficulty of access to communal wastewater treatment plant (WWTP), and the source of water around the river polluted. Conclusion: Gondomanan PHC responded to the slums dwellers needs of with implementing CLTS. Gondomanan PHC performed the functions of public health leadership through the main functions of assessment, policy development and assurance. Although there were still weaknesses in the leadership of public health, but cooperation could be improved.